2010
DOI: 10.1159/000252767
|View full text |Cite
|
Sign up to set email alerts
|

Is Autofluorescence Imaging Endoscopy Useful for Determining the Depth of Invasion in Gastric Cancer

Abstract: Background/Aims: Newly developed autofluorescence (AF) imaging (AFI) endoscopy can detect AF emitted by the gastrointestinal wall and may reliably detect tumors or inflammation that block AF. However, the efficacy of AFI endoscopy has not been evaluated for diagnosing the depth of tumor invasion in gastric cancer. Methods: AF endoscopic images were split into three bands (R, G and B) and expressed as grayscale values. AF indices, defined as the ratio of the G band image grayscale value to that of the R band, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…More than 50% of early gastric carcinoma showed well-defined pink lesions under AFI, while its surrounding mucosa showed a green background, which suggested that mucosa presented changes of atrophic gastritis. 26 Otani et al 27 used the principle of red-green hue contrast between lesions under AFI and its surrounding normal tissues, proposing the concept of “Green-Red ratio (G/R ratio).” And then their team performed AFI to detect 72 non-ulcerative gastric carcinoma lesions, finding that the average AF index of intramucosal carcinoma was 0.99, which was significantly different from that of submucosal carcinoma and invasive carcinoma, suggesting that AFI could be used to evaluate the depth of longitudinal invasion of gastric carcinoma. In the prospective cohort study of Tada et al 28 endoscopists from 2 groups, that is, the senior group and less clinical experience group (5 endoscopists in each group), evaluated 50 gastric lesions (20 early cancer lesions and 30 benign lesions) by using white-light endoscopy and AFI, respectively.…”
Section: Application Of Afi In Early Gastric Carcinomamentioning
confidence: 99%
“…More than 50% of early gastric carcinoma showed well-defined pink lesions under AFI, while its surrounding mucosa showed a green background, which suggested that mucosa presented changes of atrophic gastritis. 26 Otani et al 27 used the principle of red-green hue contrast between lesions under AFI and its surrounding normal tissues, proposing the concept of “Green-Red ratio (G/R ratio).” And then their team performed AFI to detect 72 non-ulcerative gastric carcinoma lesions, finding that the average AF index of intramucosal carcinoma was 0.99, which was significantly different from that of submucosal carcinoma and invasive carcinoma, suggesting that AFI could be used to evaluate the depth of longitudinal invasion of gastric carcinoma. In the prospective cohort study of Tada et al 28 endoscopists from 2 groups, that is, the senior group and less clinical experience group (5 endoscopists in each group), evaluated 50 gastric lesions (20 early cancer lesions and 30 benign lesions) by using white-light endoscopy and AFI, respectively.…”
Section: Application Of Afi In Early Gastric Carcinomamentioning
confidence: 99%
“…2 , 3 ). Otani et al [ 15 ] reported that AFI endoscopy was also helpful for evaluating the depth of tumor invasion in gastric cancers without ulceration.…”
Section: Autofluorescence Imagingmentioning
confidence: 99%
“…Such methods as Optical Coherence Tomography [15,16], Laser Scattering Spectroscopy [17], Raman Spectroscopy [18], Confocal Laser Endomicroscopy [19], Chromoendoscopy [20,21], Magnification Chromoendoscopy [22], Infrared Endoscopy [23] and Spectral Imaging, particularly Fluorescence Imaging including Autofluorescence Imaging (AFI) [24,25] and Narrow Band Imaging (NBI) [26] have been successfully applied in the GI tract including esophagus and stomach, for biopsy guidance and microsurgery navigation [27][28][29][30][31]. Recently, WLE, AFI and NBI have been incorporated into one system: endoscopic tri-modal imaging [32,33].…”
Section: Introductionmentioning
confidence: 99%